Effects of exercise on lipoprotein(a) - MacKinnon, L. T.; Hubinger, L. M. (Sports Medicine, 1999)
Lipoprotein(a) [Lp(a)] is a unique lipoprotein complex in the blood. At high levels (>30 mg/dl), Lp(a) is considered an independent risk factor for cardiovascular diseases. Serum Lp(a) levels are largely genetically determined, remain relatively constant within a given individual, and do not appear to be altered by factors known to influence other lipoproteins (e.g. lipid-lowering drugs, dietary modification and change in body mass). Since regular exercise is associated with favourable changes in lipoproteins in the blood, recent attention has focused on whether serum Lp(a) levels are also influenced by physical activity. Population and cross-sectional studies consistently show a lack of association between serum Lp(a) levels and regular moderate physical activity. Moreover, exercise intervention studies extending from 12 weeks to 4 years indicate that serum Lp(a) levels do not change in response to moderate exercise training, despite improvements in fitness level and other lipoprotein levels in the blood. However, recent studies suggest the possibility that serum Lp(a) levels may increase in response to intense load-bearing exercise training, such as distance running or weight lifting, over several months to years. Cross-sectional studies have reported abnormally high serum Lp(a) levels in experienced distance runners and body builders who train for 2 to 3 hours each day. However, the possible confounding influence of racial or ethnic factors in these studies cannot be discounted. Recent intervention studies also suggest that 9 to 12 months of intense exercise training may elevate serum Lp(a) levels. However, these changes are generally modest (10 to 15%) and, in most individuals, serum Lp(a) levels remain within the recommended range. It is unclear whether increased serum Lp(a) levels after intense exercise training are of clinical relevance, and whether certain Lp(a) isoforms are more sensitive to the effects of exercise training. Since elevation of both low density lipoprotein cholesterol (LDL-C) and Lp(a) levels in the blood exerts a synergistic effect on cardiovascular disease risk, attention should focus on changing lifestyle factors to decrease LDL-C (e.g. dietary intervention) and increase high density lipoprotein cholesterol (e.g. exercise) levels in the blood.